Destination Marketing and Visitor Experiences: The Development of a Conceptual Framework. Issue 6 (17th August 2016) - Jiang, Yangyang; Ramkissoon, Haywantee; Mavondo, Felix
Abstract : When confronted with increasingly experienced, demanding, and sophisticated visitors, destination marketers may find it problematic to succeed in destination marketing. This article attempts to address this challenge through the exploration of the relationship between destination image and two critical indicators of successful destination marketing: visitor delight and place attachment. It integratesdisparate themes in destination marketing and recognizes the relationshipsbetween marketing stimuli, customer experiences, and marketing outcomes. A comprehensive and coherent theoretical model is established to explain the complexities involved in the formation of important destination marketing outcomes. This article critically examines fun and customer orientation as two key concepts of visitor experiences and proposes them as principal mechanisms that mediate the relationship between destination image and visitor responses (visitor delight and place attachment). The article's theoretical contributions, limitations, and practical implications for tourism authorities and destination marketers are discussed.